Food safety research for development in sub-Saharan Africa: Tapping the expertise of German partners - Roesel, Kristina; Makita, K.; Grace, Delia (International Livestock Research Institute, 2017)
According to recent estimates by the World Health Organization, the global burden of foodborne diseases is comparable to that of HIV/AIDS or tuberculosis or malaria. Up to 90% of foodborne disease is caused by microbes in perishable foods of which more than 80% are sold in the informal agri-food system. Informal markets, also referred to as wet or traditional markets, are characterized by local products, prices, and marketing channels where actors are often not trained, not licensed, and not paying taxes. However, these markets provide food and jobs to millions of people in sub-Saharan Africa. They are also the major markets for most smallholder producers of fresh foods. Lack of evidence on attribution data and limited understanding of risk-based approaches in food safety management only worsen the problem.